SIFAT MEKANIK RUBBER WAVES DARI KOMPOSIT KARET ALAM DAN KARET SINTESIS MENGGUNAKAN MULTI FILLER - Nasruddin Nasruddin (Balai Riset dan Standardisasi Industri Palembang, 2018)
The objective of this research was to study the effect of fillers such as carbon black, caolin, and calcium carbonates on the physic-mechanical properties of rubber product (rubber waves). The design formula of this research was five formulas (A; B; C; D; and E), that designs as follows natural rubber (92; 90; 88; 84; and 80) phr; chlorprene rubber (4; 5; 6; 8; and 10); carbon black (50; 49; 48; 47; and 46) phr; caoline (10; 8; 6; 4; and 2) phr; and calcium carbonate (2; 4; 6; 8; and 10) phr respectively for each formulas. The natural and synthetics were masticated using two roll mill and then vulcanized according to the standard procedures. The best formula for rubber wave product is formula B that has properties as follows: specific gravity 1.206; hardness 71 shore A; abrasion resistance 190 mm3; 300% modulus 7.9 MPa; tensile strength 12.8 MPa; compression set 9.51%; and ozone resistance no crack.